The Transformation of Renewable Energy in Indonesia and Thailand: Energy Diversification as an Effort to Achieve the 2030 SDGs - Heriyanti, Andhina Putri; Listiaji, Prasetyo; Fibriana, Fidia; Widiyatmoko, Arif; Mustikaningtyas, Dewi; Dewi, Novi Ratna; Wiyanto, Wiyanto; Kholil, Putri Alifa; Purwadi, Cintiya Egi; Wicaksono, Maulana Malik (Universitas Negeri Semarang, 2024)
Many countries are transitioning from conventional energy to renewable energy sources. This transformation requires support through socialization and training activities targeting all sectors of society, including educators in schools. The Al-Hidayah Waqaf Foundation in Thailand is an educational institution with educators who have limited knowledge regarding the implementation of renewable energy as part of energy diversification efforts. Collaborative activities were conducted with the Al-Hidayah Waqaf Foundation in Thailand through socialization and training on renewable energy. The outcomes of these activities provided educators with increased knowledge, information, and perspectives on renewable energy.